The effects of Human-Wildlife Conflict (HWC) on mental health: the case of Shezongo Community of Kafue National Park (KNP), Zambia - Smith, Loryn Janine (Rhodes University, Faculty of Humanities, Department of Psychology)
Background: Human-wildlife conflict (HWC) is a bi-directional relationship affecting man and wild animals. Both species suffer extreme consequences, including encroachment of man into wildlife habitats and the destruction of crops and livestock by wildlife foraging for food sources. HWC is particularly prominent in Game Management Areas (GMAs), situated as buffer zones around national parks. Subsequent conflict between man and wildlife leads to not only physical harm but also psychological distress, exacerbating the consequences for mental health. Objectives: A mixed methods design was used to investigate the effects of HWC on mental health. The study aimed to determine the hidden nature of HWC within a population residing in a GMA region in Kafue National Park, Zambia. Methods: Forty-two participants took part in this study, representing a diverse range of demographic characteristics. Of these, 40 participants completed quantitative measures investigating the effect of HWC on mental health. Additionally, eight participants participated in interviews on the nature of mental health in the context of HWC. Some interview participants also completed the quantitative measures, while others did not. Thematic analysis guided qualitative investigations, while Chi-Square Analyses and Fisher's Exact Test were used to investigate the association between HWC and mental health. Results and Conclusions: The study found an association between HWC and heightened psychological distress in rural communities residing in GMA areas. Further research is required to improve the symbiotic relationship between man and wildlife, considering the consequences of HWC on human well-being and mental health.
Keywords: Human-animal relationships -- Zambia -- Kafue National Park; Human-wildlife conflict; Wildlife management areas -- Zambia; Environmental psychology; Mental health; Well-being; Human-animal relationships -- Psychological aspects